OPTIMASI PENENTUAN RUTE DAN JALUR TERAMAN PENYETORAN KAS OPERASIONAL MENGGUNAKAN METODE SHORTEST ROUTE PADA QM FOR WINDOWS - Jhon Kristopel Manalu; Dian Eka Matra Putra Bangun; Parapat Gultom (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Church financial management demands operational efficiency as well as a high level of security, particularly in physical transactional activities such as depositing congregational cash to partner banks. This study aims to determine the shortest route, fastest travel time, and safest path for conducting cash deposit activities from the Secretariat of the Methodist Church of Indonesia (GMI) Kasih Karunia to the destination bank. A quantitative approach was employed through network modeling using the Shortest Route Method, solved using the QM for Windows application. The weight variables in this network include geometric distance (meters), average travel time (minutes), and an operational security/risk vulnerability index. The results of the QM for Windows model analysis show that by integrating these three external variables, the system successfully identified the optimal route that balances logistical efficiency and street crime risk mitigation, providing a standard operational route recommendation for the church secretary.